SOME FACTORS IN THE GARMENT INDUSTRY AFFECTING THE ENVIRONMENT (Proceeding of the International Conference on Arts and Humanities, 2024)
In recent years, alongside the rapid development of technology, the material and spiritual life of people has been continuously improved; key areas such as science, economy, culture and art have all seen remarkable growth. However, this development process has also put a huge pressure on the global environment in general, and in Vietnam in particular, including contributions to pollution from the Garment and Fashion industry. The Earth is gradually warming with many alarming signs and environmental pollution in all aspects: water, air, soil, light, noise... directly affect all creatures. So how does the fashion industry truly impact the world's living environment? Garment and Fashion industry related activities, such as production processes and manufacturing materials, also contribute to environmental harm. In the context of global calls for raise awareness of environmental protection and climate change, what should we, as fashion creators and consumers, do to protect the environment, reduce waste and contribute to addressing environmental challenges as well as envisioning a sustainable future? From both practical observations and reliable data resources, Research-writer by collecting, analyzing, and describing to highlight the issues related to the current state of garment production and usage that impact the environment. From there, we provide feedbacks and solutions for the Garment and Fashion industry in general and consumers to give a hand for a more sustainable, eco-friendly Garment and fashion industry.
Keywords: the harmfulness of fabric dyeing; waste from clothing overconsumption; fashion and the environment; eco-friendly textiles; zero waste; upcycling